2018
DOI: 10.1096/fj.201701006r
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus triggers a shift from influenza virus–induced apoptosis to necrotic cell death

Abstract: Superinfections with Staphylococcus aureus are a major complication of influenza disease, causing excessive inflammation and tissue damage. This enhanced cell-damaging effect is also observed in superinfected tissue cultures, leading to a strong decrease in overall cell viability. In our analysis of the underlying molecular mechanisms, we observed that, despite enhanced cell damage in superinfection, S. aureus did not increase but rather inhibited influenza virus (IV)-induced apoptosis in cells on the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In another study, the filtered supernatant from S. aureus failed to induce apoptosis when applied to endothelial cell monolayers, thereby excluding any effect from the preformed α-toxin or other soluble bacterial factors [ 51 ]. Also, van Kruchten, Wilden [ 52 ] showed that human alveolar basal epithelial cell line (A549), bronchial epithelial cell line (Calu-3), primary human umbilical vein endothelial cells (HUVECs) and human bronchial epithelial cells (HBEpCs) infected with S. aureus alone displayed no apoptosis. Heat treating of S. haemolyticus markedly interfered with the bacterial cytotoxic potential on the PHSF cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the filtered supernatant from S. aureus failed to induce apoptosis when applied to endothelial cell monolayers, thereby excluding any effect from the preformed α-toxin or other soluble bacterial factors [ 51 ]. Also, van Kruchten, Wilden [ 52 ] showed that human alveolar basal epithelial cell line (A549), bronchial epithelial cell line (Calu-3), primary human umbilical vein endothelial cells (HUVECs) and human bronchial epithelial cells (HBEpCs) infected with S. aureus alone displayed no apoptosis. Heat treating of S. haemolyticus markedly interfered with the bacterial cytotoxic potential on the PHSF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic BAX/BAK-dependent apoptosis or caspase-9 cleavage has been reported following H5N1 and seasonal H1N1 infection of human primary type I-like alveolar epithelial cells [74], as well as PR8 infection of A549 cells [75,76], primary murine tracheal cells [77] and H7N9-infection of human blood-derived monocytes [83] (Table 2). Mechanistically, the 2009 pandemic H1N1 infection of A549 cells has been shown to promote apoptosis by downregulation of pro-survival BCL-XL [117].…”
Section: Intrinsic "Mitochondrial-dependent" Apoptosis In Iav Infectionmentioning
confidence: 99%
“…21 Research focused on the pathogenesis of S. aureus infection secondary to IAV has accumulated for these years. 9,14,18,[22][23][24][25][26][27][28][29] However, there is much less information available on MRSA pneumonia secondary to IAV infection. 30 Blyth et al 10 concluded that coinfection of IAV and bacteria synergistically aggravated inflammatory injury to the host.…”
Section: Introductionmentioning
confidence: 99%